Engineering a Highly Regioselective Fungal Peroxygenase for the Synthesis of Hydroxy Fatty Acids. (24th January 2023) - Gomez de Santos, Patricia; González‐Benjumea, Alejandro; Fernandez‐Garcia, Angela; Aranda, Carmen; Wu, Yinqi; But, Andrada; Molina‐Espeja, Patricia; Maté, Diana M.; Gonzalez‐Perez, David; Zhang, Wuyuan; Kiebist, Jan; Scheibner, Katrin; et al.
Abstract: The hydroxylation of fatty acids is an appealing reaction in synthetic chemistry, although the lack of selective catalysts hampers its industrial implementation. In this study, we have engineered a highly regioselective fungal peroxygenase for the ω‐1 hydroxylation of fatty acids with quenched stepwise over‐oxidation. One single mutation near the Phe catalytic tripod narrowed the heme cavity, promoting a dramatic shift toward subterminal hydroxylation with a drop in the over‐oxidation activity. While crystallographic soaking experiments and molecular dynamic simulations shed light on this unique oxidation pattern, the selective biocatalyst was produced by Pichia pastoris at 0.4 g L −1 in a fed‐batch bioreactor and used in the preparative synthesis of 1.4 g of (ω‐1)‐hydroxytetradecanoic acid with 95 % regioselectivity and 83 % ee for the S enantiomer. Abstract : The biocatalytic hydroxylation of fatty acids is an appealing reaction, but the generation of over‐oxidation by‐products and the lack of selectivity hampers its transfer to industry. Now a highly selective and efficient peroxygenase has been engineered for the production of hydroxy fatty acids through a synthetic procedure that can be rapidly adapted to the preparative scale.